Synergistic effects of drought and heat stress on Medicago truncatula: understanding growth response and photosynthetic mechanisms - N. Ressaissi; W. MNAFGUI; N. MAIZA; F. ZRIBI; W. ZORRIG; N. LUDIDI; M.T. SANCHEZ-BALLESTA; M. BADRI (Photosynthetica)
Drought and heat stress significantly threaten forage crop development and photosynthetic activity in the Mediterranean region. This study investigated the physiological responses and photosynthetic activity of two Medicago truncatula lines TN6.18 and F83005.5 (F83), to single and combined heat and drought stress treatments. Biomass traits, leaf gas exchange, and photosystem activities were evaluated. Our findings indicate a reduction in biomass parameters under heat, drought, and combined stress on both lines, particularly in F83. The stomatal conductance and photosynthetic parameters exhibited differential responses, with F83 reducing its stomatal conductance under drought stress, while TN6.18 was adapted by opening its stomata. Moreover, in TN6.18, combined stress enhanced protection mechanisms in PSI, while F83 showed changes in PSII efficiency. These insights deepen our understanding of plant responses to abiotic stresses and offer strategies for improving tolerance and resilience in changing environmental conditions.